The Comprehension of STEM Graphics via a Multisensory Tablet Electronic Device by Students with Visual Impairments. (September 2019) - Hahn, Michael E.; Mueller, Corrine M.; Gorlewicz, Jenna L.
Introduction: The current work probes the effectiveness of multimodal touch screen tablet electronic devices in conveying science, technology, engineering, and mathematics graphics via vibrations and sounds to individuals who are visually impaired (i.e., blind or low vision) and compares it with similar graphics presented in an embossed format. Method: A volunteer sample of 22 participants who are visually impaired, selected from a summer camp and local schools for blind students, were recruited for the current study. Participants were first briefly (∼30 min) trained on how to explore graphics via a multimodal touch screen tablet. They then explored six graphic types (number line, table, pie chart, bar chart, line graph, and map) displayed via embossed paper and tablet. Participants answered three content questions per graphic type following exploration. Results: Participants were only 6% more accurate when answering questions regarding an embossed graphic as opposed to a tablet graphic. A paired-samples t test indicated that this difference was not significant, t (14) = 1.91, p = .07. Follow-up analyses indicated that presentation medium did not interact with graphic type, F (5, 50) = 0.43, p = .83, nor visual ability, F (1, 13) = 0.00, p = .96. Discussion: The findings demonstrate that multimodal touch screen tablets may be comparable to embossed graphics in conveying iconographic science and mathematics content to individuals with visual impairments, regardless of the severity of impairment. The relative equivalence in response accuracy between mediums was unexpected, given that most students who participated were braille readers and had experience reading embossed graphics, whereas they were introduced to the tablet the day of testing. Implications for practitioners: This work illustrates that multimodal touch screen tablets may be an effective option for general education teachers or teachers of students with visual impairments to use in their educational practices. Currently, preparation of accessible graphics is time consuming and requires significant preparation, but such tablets provide solutions for offering "real-time" displays of these graphics for presentation in class.